High-Dose-Rate Brachytherapy as Monotherapy for Low- and Intermediate-Risk Prostate Cancer. Oncological Outcomes After a Median 15-Year Follow-Up - Behmueller, Manuel; Tselis, Nikolaos; Zamboglou, Nikolaos; Zoga, Eleni; Baltas, Dimos; Rödel, Claus; Chatzikonstantinou, Georgios (Frontiers in Oncology, 2021)
Introduction To evaluate the oncological outcome of high dose rate (HDR) brachytherapy (BRT) as monotherapy for clinically localised prostate cancer (PCA). Material and Methods Between January 2002 and February 2004, 141 consecutive patients with clinically localised PCA were treated with HDR-BRT monotherapy. The cohort comprised 103 (73%) low-, 32 (22.7%) intermediate- and 6 (4.3%) high risk patients according to D’Amico classification or 104 (73.8%) low-, 24 (17.0%) intermediate favourable-, 12 (8.5%) intermediate unfavourable- and one (0.7%) very high risk patient according to National Comprehensive Cancer Network (NCCN) one. Patients received four fractions of 9.5 Gy delivered within a single implant up to a total physical dose of 38 Gy. Catheter-implantation was transrectal ultrasound-based whereas treatment planning CT-based. Thirty-three patients (23.4%) received ADT neoadjuvantly and continued concurrently with BRT. Biochemical relapse-free survival (BRFS) was defined according to the Phoenix Consensus Criteria and genitourinary (GU)/gastrointestinal (GI) toxicity evaluated using the Common Toxicity Criteria for Adverse Events version 5.0. Results Median age at treatment and median follow-up time was 67.2 and 15.2 years, respectively. Twenty-three (16.3%) patients experienced a biochemical relapse and 5 (3.5%) developed distant metastases, with only one patient dying of PCA. The BRFS was 85.1% at 15 years and 78.7% at 18 years. The corresponding overall survival, metastases-free survival, and prostate cancer specific mortality at 15- and 18-years was 73.9%/59.1%, 98.3%/90.6%, and 100%/98.5% respectively. Late grade 3 GI and GU toxicity was 4.2% and 5.6% respectively. Erectile dysfunction grade 3 was reported by 27 (19%) patients. From the prognostic factors evaluated, tumor stage (≤T2b compared to ≥T2c) along with the risk group (low-intermediate vs. high) when using the D’Amico classification but not when the NCCN one was taken into account, correlated significantly with BRFS. Conclusion Our long-term results confirm HDR-BRT to be a safe and effective monotherapeutic treatment modality for low- and intermediate risk PCA.